Innovations in child welfare interventions for caregivers with substance use disorders and their children. (June 2019) - Bosk, Emily A.; Paris, Ruth; Hanson, Karen E.; Ruisard, Debra; Suchman, Nancy E.
Abstract: Families who enter the Child Welfare System (CWS) as a result of a caregiver's substance use fare worse at every stage from investigation to removal to reunification (Marsh, Smith, & Bruni, 2011 ). Intervening with caregivers with Substance Use Disorders (SUDs) and their children poses unique challenges related to the structure and focus of the current CWS. Research demonstrates that caregivers with SUDs are at a greater risk for maladaptive parenting practices, including patterns of insecure attachment and difficulties with attunement and responsiveness (Suchman, Paulo, DeCoste, & Mayes, 2006 ). Caregivers with SUDs have also often experienced early adversity and trauma. However, traditional addiction services generally offer limited opportunities to focus on parenting or trauma, and traditional parenting programs rarely address the special needs of parents with SUDs. This article details four innovative interventions that integrate trauma-informed addiction treatments with parenting for families involved in the child welfare system. Common mechanisms for change across programs are identified as critical components for intervention. This work suggests the need for a paradigm shift in how cases involving caregivers with substance use disorders are approached in the child welfare system. Highlights: Cases in the child welfare system involving caregiver substance use disorder(s) need new approaches. Relationship-focused interventions offer new opportunities to keep families together during recovery and to improve child welfare outcomes. Four innovative models: Project BRIGHT, Family-Based Recovery, C.A.R.E. and Mothering From the Inside Out are described. Common mechanisms for change are identified: 1) increasing caregiver reflective functioning; 2) increasing caregiver and child emotional regulation capacities and; 3) increasing the quality of parent-child relationships through strengthening caregiver responsiveness, sensitivity, and attunement. These targets contribute not just to greater parenting capacities but also to maintaining sobriety.